Thresholds of energy security metrics: their purpose and assessment techniques - Kononov Yuri; Kononov Dmitrii (E3S Web of Conferences, 2023)
The study discusses the issue of enhancing the validity of projections of energy sector development by properly accounting for the effect of available options on energy security. To this end, it is possible to use a single overall index that measures the degree of deviation of individual energy security metrics from their threshold values. We detail different ways of calculating maximum allowable values of individual metrics. The study also provides the results of modeled calculations. We argue that any indicator-based analysis of thresholds should be preceded by an assessment of strategic energy security threats and identification of the stability range for the dynamics of key projected indicators.